Older migrants’ critical moments: retirement transition and decision-making on return migration. The case of Portuguese in Switzerland - Azevedo, L. (Congress of the Swiss Sociological Association, 2019)
Portuguese are the third more numerous foreign-born population group in Switzerland, but little is known about them. The country became a major destination for Portuguese labour migrants in the 1980’s. Although the Swiss migration regime was restrictive, a significant number of those migrants took spouses and children with them, legally or illegally, and spent their entire working life in Switzerland. Oldest Portuguese migrants are now over 60 and face an overlapping of critical moments: retirement transition and return migration decision-making, which sometimes bring tensions within the couple. Among other factors, personal resources, health conditions, family configurations, as well as political and institutional arrangements in both countries (i.e. pension regimes, health and tax systems) have to be taken into consideration to draw the overall framework of complex influences in post-retirement mobility decisions. Three main options are usually subject to negotiation within the couple (or the family): ageing in place, returning to Portugal or going back and forth between both countries. These matters raise many questions, including: are those migrants more or less transnational after retirement? Do migrants who acquired the Swiss citizenship address those issues in a different way? What role does gender play in the decision-making process on mobility choices after retirement? I will present some elements of reflection from the on-going doctoral multi-sited research, based on the in-depth interviews conducted up till now, both in Portugal and Switzerland, with Portuguese migrants over 60 years old in retirement transitions or already retired.